Sporting Facts - Lapage, Ginny (Collins Educational, 1990)
People have played or watched sport and games for thousand of years.In wartime or when hunting food,people needed to learning skills.This is how most sports and games started.
Keywords: English Language; Readers (Primary); Reading (Primary); Sports